WOMEN LEADERSHIP IN ACEHNESE MUFASSIR'S PERSPECTIVE: A COMPARISON OF ABDURRAUF AS-SINGKILY AND HASBI AS-SHIDDIEQY'S INTERPRETATION - Amin, Muhammad (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2022)
Women's leadership is still a controversial topic among the Acehnese ulama. Abdurrauf as-Singkily and Muhammad Hasbi ash-Shiddieqy are two other Acehnese ulama and commentators who commented on this topic. Both have worked in the field of interpretation. This study aims to compare both perspectives on women's leadership. The research uses a comparative interpretation methodology (muqarran). The study also uses hermeneutic methods to analyze the influence behind the interpretation of the two commentators in their works. The study results concluded that Abdurrauf as-Singkily and Muhammad Hasbi ash-Shiddieqy had similar views on women's leadership. According to them, in the domestic area (household), the leadership is on the husband's side (male). Meanwhile, in the public sphere, both believe that men and women have equal opportunities to become leaders.